Stale administration and execution powcr:correlation tendency of modern development - Діхтієвський, Петро Васильович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
This article shows us the basic position of optimization state management.also increasing authorities. Scitntific position of scientists — their attitude are administrative for structual mechanism of executivepower, division such concepts as "goverment" and "executiv power".